Problems in Arabic Language Learning: Challenges in Implementing the Curriculum at Ma'had Muslimeen Care Academy Malaysia - Usriya Hasna Agustin; Akhmad Shaiful Bakri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the problems of Arabic language learning as a challenge in implementing the curriculum at Ma'had Muslimeen Care Academy (MCA), Malaysia. The study uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation of educators, ma'had caregivers, students, the learning process in the classroom, and institutional documents. This study was motivated by the condition of MCA as an Islamic educational institution that is still in its early stages and has adopted the Arabic language curriculum of Kulliyatul Mu'allimin Al-Islamiyah (KMI) Pondok Modern Darussalam Gontor, which has a different social and institutional context. The results of the study show a gap between the principle of mubāsyarah learning, which emphasizes the communicative and intensive use of Arabic, and classroom learning practices. This gap is influenced by various contextual factors, both institutional and learning-related. The findings of this study indicate that the implementation of the Arabic language curriculum at MCA does not take place linearly, but rather through a process of curriculum enactment that is negotiated in accordance with institutional conditions, student characteristics, and available resources. Unlike previous studies, this study emphasizes the analysis of the problems of Arabic language learning in the context of Islamic educational institutions that are still in the pioneering stage, by paying attention to the interrelationship between institutional, curricular, and learning aspects in an integrative manner. This study provides a theoretical contribution by enriching the study of Arabic language learning through the perspective of curriculum enactment in the context of pioneering Islamic boarding schools, as well as a practical contribution to the development of Arabic language curriculum management to be more in line with the institutional context and the needs of students, especially in Islamic educational institutions in Malaysia.